Robust finite-time H∞ filtering for uncertain systems subject to missing measurements - Deng, Zhenghong (Journal of inequalities and applications, 2013)
In this paper, the robust finite-time H ∞ filter design problem for uncertain systems subject to missing measurements is investigated. It is assumed that the system is subject to the norm-bounded uncertainties and the measurements of the output are intermittent. For the model of the missing measurements, the Bernoulli process is adopted. A full-order filter is proposed to estimate the signal which can track the signal to be estimated. By augmenting the system vector, a stochastic augmented system is obtained. Based on the analysis of the robust stochastic finite-time stability and the H ∞ performance, the filter design method is obtained. The filter parameters can be calculated by solving a sequence of linear matrix inequalities. Finally, a numerical example is used to show the design procedure and the effectiveness of the proposed design approach.